Integrasi Nilai Al-Qur'an dalam Manajemen Pendidikan Islam di Era Digital - Yuli Supodo; Hasnida Hasnida (SENTRI: Jurnal Riset Ilmiah, 2025)
This study investigates the integration of Qur'anic values into Islamic education management in the digital era, addressing critical challenges such as technology adaptation gaps among educators (52% access disparity), limited Qur'anic managerial understanding, and resource constraints in modern institutions. The research significance lies in bridging theoretical Islamic principles with digital tools to enhance efficiency, relevance, and ethical management amid rapid technological disruption affecting 70% of Indonesian madrasah. Employing qualitative library research with descriptive-analytical design, content analysis of 25 thematic Qur'anic verses (tafsir mawdhu'i), and triangulation of 35 recent Sinta journals (80% post-2015), the study examines POAC functions: planning [QS. Al-Anfal:60], organizing [QS. An-Nisa:58], actuating [QS. Al-Jumu'ah:9-10], and controlling [QS. Al-Hasyr:18]. Key findings reveal 82% relevance of Qur'anic integration, yielding 37% overall management efficiency gains: 42% planning time reduction, 56% prediction accuracy via AI curriculum planners, equity score 0.87 in cloud sharing (disparity drop from 52% to 12%), 41% hafalan retention via hybrid Zoom-tilawah, and 92% monitoring accuracy with taqwa KPIs. Correlations range r=0.68-0.82 (p<0.01), explaining 68% efficiency variance (R²=0.68), confirming synergistic Qur'ani-digital models. These results underscore the transformative potential of proactive Qur'anic management paradigms, recommending national hybrid curricula, manager certifications, and scalable mobile apps. This framework positions Islamic education as technology shaper rather than responder, ensuring resilient, ethical institutions for Indonesia's digital future.